Catalyst with core-shell structure as well as preparation method and application of catalyst

A core-shell structured catalyst with a cerium oxide core and La2O3/Ni shell addresses nickel agglomeration issues, enhancing catalytic performance and stability in tar and CO2 reforming by improving dispersion and reducing carbon deposition.

CN119158580APending Publication Date: 2024-12-20NANKAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411086243.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-08
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing catalysts for tar and CO2 reforming suffer from poor catalytic performance due to nickel migration and agglomeration, low surface area, and lack of internal pores, which limits their effectiveness in high-temperature reactions.

Method used

A core-shell structured catalyst is developed, where the core is spherical cerium oxide with lattice distortion and the shell layer comprises La2O3 and Ni, with specific molar ratios, prepared through a method involving hydrothermal reaction and calcination to enhance dispersion and stability.

Benefits of technology

The catalyst exhibits high conversion rate, selectivity, and stability, with improved metal dispersion and reduced carbon deposition, suitable for tar and CO2 reforming processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158580A_ABST
    Figure CN119158580A_ABST
Patent Text Reader

Abstract

The invention relates to the field of tar and CO2 reforming, in particular to a catalyst with a core-shell structure as well as a preparation method and application of the catalyst. Wherein lattice-distorted spherical cerium oxide is used as a core, and a shell layer comprises La2O3 and Ni; in the lattice-distorted spherical cerium oxide, the content of Ce < 3 + > is 18-25 wt%, and the content of Ce < 4 + > is 72-85 wt%; ce < 3 + > and Ce < 4 + > exist in the cerium-containing oxide at the same time, lattice distortion of the cerium-containing oxide is proved, the specific content of Ce < 3 + > and Ce < 4 + > ensures that the catalyst has more oxygen vacancies and can be used as catalytic sites, the catalyst is used in the fields of tar treatment and CO2 reforming, and the catalyst has high conversion rate and selectivity, meanwhile, is good in stability and can be used for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of tar and CO2 reforming, and in particular to a core-shell structured catalyst and a preparation method and application thereof. Background Art

[0002] Gasification process is a promising new carbon-neutral technology for thermochemical conversion of renewable biomass, which can produce syngas for power generation and synthetic fuels. However, the syngas produced contains not only H2 and CO, but also a large amount of tar and CO2 byproducts. The thermal catalytic reforming technology of tar and CO2 can simultaneously convert tar and CO2 byproducts into syngas, which is crucial for the upgrading and utilization of biomass gasification technology. The key to the reforming of tar and CO2 is to develop functional catalysts that are efficient, resistant to metal sintering and carbon deposition.

[0003] Supported nickel-based catalysts have become the most studied and industrially promising catalysts in the field of tar and CO2 reforming technology due to their high reserves in nature, low cost, and good catalytic performance in reforming reactions. The traditional impregnation method can directly deposit the nickel precursor on the surface of the support, but the interaction between nickel and the support is weak, and the nickel particles will further migrate and agglomerate during the subsequent high-temperature treatment and reduction process. Therefore, the nickel-based catalysts prepared by the traditional impregnation method have poor metal dispersion, large size, and are more prone to sintering and deactivation at high temperatures, which restricts development. Some certain structural materials, such as perovskite, spinel, hydrotalcite, and molecular sieves, have attracted much attention due to their improved nickel dispersion and enhanced metal-support interaction, which is conducive to suppressing nickel aggregation and coking problems in tar reforming. Among them, perovskite (ABO3, where A and B usually represent trivalent rare earth cations and transition metals, respectively) has become a potential catalyst precursor due to its excellent thermal and hydrothermal stability and easily adjustable physical and chemical properties. Through proper reduction, the transition metals in the perovskite B site can be dissolved into finely dispersed nanoparticles dispersed on the highly stable oxide.

[0004] Although perovskites have advantages as catalyst host materials, they usually have low surface areas and no internal pores, which limits their access to reactants and intermediates. Distributing perovskites on support materials with high specific surface areas is an attractive strategy to address the above limitations.

[0005] Although numerous studies have emphasized the effect of CeO2 morphology on catalytic performance, there are few reports on the use of nanostructured CeO2-supported perovskite-derived core-shell catalysts in reforming reactions, especially in CRT reactions.

[0006] Existing technologies generally focus on the reforming of water vapor and tar, and there is less research on the reforming of tar and CO2. Compared with the tar steam reforming process (SRT formula 2), the tar-CO2 reforming process (CRT formula 1) has less energy input during water evaporation and a lower H2 / CO ratio in the generated synthesis gas. However, the CRT reaction is highly endothermic and needs to be carried out under high temperature conditions. In addition, compared with SRT, the CRT reaction has a higher carbon-hydrogen ratio and is more prone to carbon deposition.

[0007] C x H y O z + (xz)CO2 → (2x-z)CO + y / 2H2 ΔH0> 0 (1)

[0008] C x H y O z + (xz)H2O → xCO+ (x+y / 2-z)H2 ΔH0> 0 (2)

[0009] Therefore, it is very necessary to design a catalyst with high conversion rate and selectivity for treating tar and CO2 reforming. Summary of the invention

[0010] Therefore, the technical problem to be solved by the present invention is to overcome the defect of poor catalytic effect of existing catalysts on the reforming of tar and CO2, thereby providing a core-shell structured catalyst and a preparation method and use thereof.

[0011] The first aspect of the present invention protects a core-shell structure catalyst, wherein the core is a spherical cerium oxide with a lattice distortion, and the shell layer includes La2O3 and Ni;

[0012] In the spherical cerium oxide with lattice distortion, Ce 3+ Content is 18-25wt%, Ce 4+ The content is 72-85wt%.

[0013] In the present invention, X-ray photoelectron spectroscopy (XPS) is used to detect Ce in cerium-containing oxides. 3+ and Ce 4+ The content of cerium in CeO2 and the presence of cerium in different valence states in cerium-containing oxides prove that lattice distortion occurs in CeO2. XPS was performed using a Thermo Scientific K-Alpha+ instrument equipped with an Al Kα X-ray radiation source (hυ=1486.6eV) at a power of 225W (15kV, 15mA). The raw data was calibrated using carbon C1s with a binding energy of 284.6eV.

[0014] According to the present invention, when the catalyst contains only Ce, La and Ni, the molar ratio of Ce in the spherical cerium oxide, La in La2O3 and Ni is (0.03-0.08):0.02:0.02, preferably (0.038-0.06):0.02:0.02.

[0015] In the present invention, the amount of each element is made to satisfy the molar ratio through precise material feeding design.

[0016] According to the present invention, the shell layer of the catalyst also includes Co; when Co is contained, the molar ratio of the Ce element in the spherical cerium oxide, the La element in La2O3, the Ni element and the Co element is (0.03-0.08):(0.01-0.02):(0.01-0.02):(0.005-0.008).

[0017] According to the present invention, the specific surface area of ​​the catalyst is 35-45m 2 ·g -1 , pore volume is 0.14-0.25cm 3 ·g -1 , pore size is 20-25nm.

[0018] In the present invention, the specific surface area, pore volume and pore size of the catalyst are detected by the specific surface area detection method (BET). A N2 physical adsorption-desorption experiment is carried out at -196°C using a Micromeritics ASAP 2460 adsorption device to determine the specific surface area, pore volume and pore size of the reduced catalyst.

[0019] The second aspect of the present invention protects a method for preparing a core-shell structured catalyst, wherein the preparation method comprises:

[0020] S1, adding a cerium source to a first solvent, mixing for a first time, performing a hydrothermal reaction, and then performing a first calcination to obtain spherical cerium oxide;

[0021] S2, mixing the spherical cerium oxide, lanthanum source, nickel source, citric acid and the second solvent for a second time, drying to obtain a gel, calcining for a second time, and reducing to obtain a core-shell structure catalyst.

[0022] In the present invention, after the second calcination, the lanthanum source and the nickel source form a product (LaNiO3) with a perovskite structure, which exists in the form of La2O3 and Ni after reduction and is dispersed in the spherical cerium oxide, thereby overcoming the shortcomings of the perovskite type such as low specific surface area and lack of internal pores.

[0023] In the present invention, the type and amount of the second solvent are not limited, as long as the reaction can proceed smoothly. Typically, but not limiting, the second solvent is ethanol.

[0024] According to the present invention, the cerium source is an inorganic salt containing cerium, preferably at least one of Ce(NO3)3·6H2O, Ce(NO3)3, and CeCl3.

[0025] According to the present invention, the first solvent includes water, an organic acid and ethylene glycol.

[0026] In the present invention, the cerium source and the solvent may be added together, or the cerium source may be first added to water and an organic acid, and then ethylene glycol may be added.

[0027] According to the present invention, the dosage ratio of the cerium source to water is (5-6):(5-7), and the unit is g / mL.

[0028] According to the present invention, the volume ratio of water, organic acid and ethylene glycol is 5:(5-7.5):(90-100).

[0029] In the present invention, the water is regular water, preferably deionized water.

[0030] According to the present invention, the organic acid comprises acetic acid and / or propionic acid.

[0031] According to the present invention, the temperature of the first mixing is 25-30° C. and the time is 20-40 min.

[0032] According to the present invention, the temperature of the hydrothermal reaction is 155-165° C. and the time is 7.5-8.5 hours.

[0033] In the present invention, the product obtained after hydrothermal treatment is also centrifuged and washed at a centrifugal speed of 4000-7000 rpm, and dried at 80-110° C. for 12-24 hours.

[0034] According to the present invention, the first calcination is carried out by heating the material to 550-650° C. at a heating rate of 5-10° C. / min for 5-7 hours.

[0035] According to the present invention, the molar ratio of the Ce element in the spherical cerium oxide, the La element in the lanthanum source, and the Ni element in the nickel source is (0.03-0.08):0.02:0.02, preferably (0.038-0.06):0.02:0.02.

[0036] According to the present invention, when the spherical cerium oxide, lanthanum source, nickel source, cobalt source, citric acid and second solvent are mixed for the second time, the molar ratio of the Ce element in the spherical cerium oxide, the La element in the lanthanum source, the Ni element in the nickel source and the Co element in the cobalt source is (0.03-0.08):(0.01-0.02):(0.01-0.02):(0.005-0.008).

[0037] According to the present invention, the lanthanum source is an inorganic salt containing lanthanum, typically but not limitedly, including at least one of La(NO3)3·6H2O, La(NO3)3, and LaCl3.

[0038] According to the present invention, the nickel source is an inorganic salt containing nickel, typically but not limitedly, including at least one of Ni(NO3)2·6H2O, Ni(NO3)2, and NiCl2.

[0039] According to the present invention, the cobalt source includes an inorganic salt containing cobalt, typically but not limited to, at least one of Co(NO3)2·6H2O, Co(NO3)2, and CoCl2.

[0040] According to the present invention, the molar ratio of the citric acid to the sum of the La element in the lanthanum source and the Ni element in the nickel source is 1-2:1, preferably 1.2-1.5:1; the sum here is the sum of the La element in the lanthanum source and the Ni element in the nickel source.

[0041] According to the present invention, the temperature of the second mixing is 25-30° C. and the time is 20-40 min.

[0042] According to the present invention, the specific steps of drying are as follows: first evaporating at 75-85° C., and then drying at 90-110° C. for 12-24 hours.

[0043] According to the present invention, the temperature is raised to 350-400° C. at a heating rate of 5-10° C. / min and calcined for 1-1.5 h, and then the temperature is raised to 800-870° C. at a heating rate of 5-10° C. / min and calcined for 5-7 h.

[0044] According to the present invention, the reduction conditions include: heating to 600-700°C at a rate of 5-15°C / min for reduction, for 1-2.5h, and a hydrogen rate of 15-25mL / min.

[0045] The third aspect of the present invention protects the use of the aforementioned catalyst or the catalyst prepared by the aforementioned preparation method in the reforming of tar and CO2.

[0046] According to the present invention, the specific catalytic process is a conventional catalytic method in the art. Typically, the catalyst is supported by quartz wool and placed in the middle of a quartz tube (600 mm in length and 25 mm in diameter), and the quartz tube is placed in the heating zone of a vertical heating furnace. The amount of catalyst used in each experiment is 50-60 mg to CO2 (5-10 mL / min) and N2 (40-45 mL / min). C7H8 is used as a model tar compound and is injected into the reaction system at a speed of 5-6 μL / min through an injection pump. Toluene is gasified by a heating belt (180-200°C) device and enters the reactor together with a mixture of CO2 and N2. The product is determined by online gas chromatography.

[0047] The technical solution of the present invention has the following advantages:

[0048] 1. The present invention provides a core-shell structure catalyst, wherein the core is a spherical cerium oxide with a lattice distortion, and the shell layer comprises La2O3 and Ni; in the spherical cerium oxide with a lattice distortion, Ce 3+ Content is 18-25wt%, Ce 4+ The content is 72-85wt%; Ce also exists in cerium oxide 3+ With Ce 4+ It proves that cerium oxide does undergo lattice distortion. 3+ With Ce 4+ The specific content ensures that the catalyst has more oxygen vacancies, which can be used as catalytic sites and used in the fields of tar treatment and CO2 reforming. The catalyst has a high conversion rate and selectivity, and is also stable and can be used for a long time.

[0049] 2. In the present invention, the Ce element in the spherical cerium oxide, the La element in La2O3, and the Ni element in Ni have a specific molar ratio. A portion of the La element in the catalyst increases the degree of lattice distortion. 4+ Part of it is reduced to Ce 3+ , oxygen vacancies accelerate interfacial electron transfer and promote the adsorption and activation of carbon dioxide, thereby providing a large amount of surface active oxygen, which is beneficial to the elimination of carbon deposits.

[0050] 3. The specific surface area, pore volume and pore size of the catalyst in the present invention can further improve the dispersion of metal particles, promote the adsorption capacity of the catalyst to surface reactants, and accelerate the catalytic reaction.

[0051] 4. The present invention provides a preparation method, which specifically comprises the following steps: S1, adding a cerium source to a first solvent and mixing for the first time, performing a hydrothermal reaction, and then performing a first calcination to obtain spherical cerium oxide; S2, mixing the spherical cerium oxide, a lanthanum source, a nickel source, citric acid, and a second solvent for the second time, drying to obtain a gel, and performing a second calcination to obtain a core-shell structure catalyst; the present invention adopts in-situ synthesis, so that part of the La element in the lanthanum source is doped into the lattice of the spherical cerium oxide, and since the radius of the doped ions is similar to that of Ce, 4+ The difference in ionic radius will cause stress inside the lattice, which in turn causes lattice distortion and increases the content of oxygen vacancies. The resulting catalyst has excellent conversion rate, selectivity and stability.

[0052] 5. The specific hydrothermal conditions of the present invention can enable the nucleation and uniform growth of cerium dioxide balls, prepare uniformly dispersed cerium dioxide balls, and prevent cerium dioxide from agglomerating.

[0053] 6. The specific first calcination conditions of the present invention can achieve a larger specific surface area and more pore structures of cerium dioxide, thereby increasing the specific surface area and pore size of the composite material and accelerating the reaction.

[0054] 7. The specific second calcination conditions of the present invention can further improve the conversion rate and selectivity of the catalyst. The inventors speculate that this may be because the second calcination temperature affects the movement speed of molecules or atoms and increases the collision probability of molecules or atoms, which increases the internal stress of the lattice and ultimately affects the degree of lattice distortion. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0056] Figure 1 is an electron microscope image of Ni@La2O3-CeO2-NS of Example 1;

[0057] Figure 2 is the EDX image of Ni@La2O3-CeO2-NS of Example 1;

[0058] Figure 3 It is an electron microscope image of Ni / La2O3-CeO2-NP of comparative example 1;

[0059] Figure 4 is the EDX image of Ni / La2O3-CeO2-NP of Comparative Example 1;

[0060] Figure 5 It is the XRD spectrum of the product after the second calcination of Example 1, Comparative Example 1 and Comparative Example 2;

[0061] Figure 6 The XRD patterns of the final products obtained in Example 1, Comparative Example 1 and Comparative Example 2 are shown in FIG.

[0062] Figure 7 The XRD spectra of the catalysts after catalytic reaction of Example 1, Comparative Example 1 and Comparative Example 2;

[0063] Figure 8 It is the Raman spectra of Example 1, Comparative Example 1 and Comparative Example 2;

[0064] Fig. 9 TG curves of Example 1, Comparative Example 1 and Comparative Example 2;

[0065] Fig.10 It is the DSC curve of Example 1, Comparative Example 1 and Comparative Example 2. DETAILED DESCRIPTION

[0066] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0067] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0068] The ethanol in the embodiments and comparative examples is anhydrous ethanol, and the water is deionized water.

[0069] Example 1

[0070] This embodiment provides a core-shell structure catalyst and a preparation method thereof, which are as follows:

[0071] S1. Dissolve 5 g of Ce(NO3)3·6H2O in 5 mL of water and 5 mL of propionic acid and then add 90 mL of ethylene glycol for the first mixing. The temperature of the first mixing is 25°C and the time of the first mixing is 20 min. Perform a hydrothermal reaction at a temperature of 160°C and a time of 8 h. Wash by centrifugation, dry at 100°C for 24 h, and heat to 600°C at a heating rate of 10°C / min for the first calcination for 6 h.

[0072] S2, 0.06 mol of spherical cerium oxide, 0.02 mol of La(NO3)3·6H2O, 0.02 mol of Ni(NO3)2·6H2O and 50 mL of ethanol were mixed for the second time at a mixing temperature of 25°C for a mixing time of 20 min, and then citric acid was added, the molar ratio of citric acid to the total amount of La element in La(NO3)3·6H2O and Ni element in Ni(NO3)2·6H2O was 1.2:1, and the mixture was evaporated at 80°C to obtain a wet gel, which was dried at 100°C for 24 h to obtain a dry gel, and then calcined for the second time in a muffle furnace, heated to 380°C at a heating rate of 10°C / min for 1 h, and then heated to 850°C at a heating rate of 10°C / min for 6 h, cooled to room temperature to obtain an oxide, and then heated to 600°C at a rate of 10°C / min for reduction for 1 h, with a hydrogen rate of 20 mL / min, to obtain Ni@CeLaO x -NS, specific appearance Figure 1 ,from Figure 1 It can be seen that Ni@CeLaO x -NS is spherical; from Figure 3 It can be seen that the distribution of Ce, La, and Ni elements is similar, indicating that La is easily doped into the CeO2 lattice, inducing lattice distortion and defects; Figure 5 , Figure 6 It can also be proved that CeO2 does undergo lattice distortion. The diffraction peaks of all samples (except LaNiO3) can be marked as the face-centered cubic structure of CeO2, while the diffraction peak of the (111) plane in the curve shows obvious differences. Figure 5 It can be seen from the enlarged XRD pattern that the diffraction peak of the sample in Example 1 is shifted to a lower 2θ value than that of the sample in Comparative Example 1, which indicates that more La 3+ It has been successfully doped into the CeO2 lattice. In addition, compared with pure CeO2, the diffraction peak height of CeO2 in the catalyst of Example 1 is reduced, which is due to the increase in lattice defects caused by the insertion of La elements. 4+ In comparison, La 3+ The addition of will induce the formation of more Ce 3+ To compensate for the lattice distortion effect, which forms defect points and vacancies.

[0073] Example 2

[0074] This embodiment provides a core-shell structured catalyst and a preparation method thereof. Compared with Embodiment 1, the difference is that in step S2, 0.032 mol of spherical cerium oxide, 0.02 mol of La(NO3)3·6H2O, 0.02 mol of Ni(NO3)2·6H2O and 50 mL of ethanol are mixed for a second time.

[0075] Example 3

[0076] This embodiment provides a core-shell structured catalyst and a preparation method thereof. Compared with Example 1, the difference is that in step S2, 0.06 mol of spherical cerium oxide, 0.02 mol of La(NO3)3·6H2O, 0.014 mol of Ni(NO3)2·6H2O and 0.006 mol of Co(NO3)2·6H2O are mixed with 50 mL of ethanol for a second time.

[0077] Example 4

[0078] This embodiment provides a core-shell structure catalyst and a preparation method thereof. Compared with Example 1, the difference is that in step S2, the molar ratio of citric acid to the total amount of La element in La(NO3)3·6H2O and Ni element in Ni(NO3)2·6H2O is 2:1.

[0079] Example 5

[0080] This embodiment provides a core-shell structured catalyst and a preparation method thereof. Compared with Embodiment 1, in step S1, the difference is that the hydrothermal temperature is 165° C. and the hydrothermal time is 8.5 h.

[0081] Example 6

[0082] This embodiment provides a core-shell structured catalyst and a preparation method thereof. Compared with Embodiment 1, the difference is that in step S1, the temperature is raised to 630° C. at a heating rate of 9° C. / min for the first calcination for 5.5 h.

[0083] Example 7

[0084] This embodiment provides a core-shell structured catalyst and a preparation method thereof. Compared with Embodiment 1, the difference is that in step S2, the temperature is raised to 400°C at a heating rate of 10°C / min and calcined for 1.5 hours, and then the temperature is raised to 870°C at a heating rate of 8°C / min and calcined for 5.5 hours.

[0085] Example 8

[0086] This embodiment provides a core-shell structure catalyst and a preparation method thereof. Compared with Embodiment 1, the difference is that in step S2, the temperature is raised to 700°C at a rate of 5°C / min for reduction for 1 hour, and the hydrogen rate is 25 mL / min.

[0087] Comparative Example 1

[0088] This comparative example provides a catalyst and a preparation method thereof, which are as follows:

[0089] S1. Under air atmosphere, 5 g of Ce(NO3)3·6H2O was calcined in a muffle furnace at 350°C for 4 h to obtain CeO2-NP; 0.06 mol of CeO2-NP was dispersed in 50 mL of ethanol and ultrasonicated for 20 min.

[0090] S2. Mix the ultrasonic CeO2-NP, 0.02 mol La(NO3)3·6H2O, 0.02 mol Ni(NO3)2·6H2O and ethanol at a mixing temperature of 25°C for 20 min, then add citric acid, the molar ratio of citric acid to the total amount of La element in La(NO3)3·6H2O and Ni element in Ni(NO3)2·6H2O is 1.2:1, evaporate at 80°C to obtain wet gel, dry at 100°C for 24 h to obtain dry gel, and calcine, first heat to 380°C at a heating rate of 10°C / min and calcine for 1 h, then heat to 850°C at a heating rate of 10°C / min and calcine for 6 h, cool to room temperature to obtain oxide, then heat to 600°C at a rate of 10°C / min for reduction for 1 h, and the hydrogen rate is 20 mL / min to obtain Ni / La2O3-CeO2-NP, the specific morphology is as follows: Figure 2 ,from Figure 2 It can be seen that Ni / La2O3-CeO2-NP is not spherical; Figure 4 It can be seen that the distribution of La and Ni elements is similar, but different from that of Ce element, which means that La element is difficult to incorporate into the Ce lattice.

[0091] Comparative Example 2

[0092] This comparative example provides a catalyst and a preparation method thereof, which are as follows:

[0093] 0.02 mol of La(NO3)3·6H2O, 0.02 mol of Ni(NO3)2·6H2O and 50 mL of ethanol were mixed at a mixing temperature of 25°C and a mixing time of 20 min. Citric acid was then added, and the molar ratio of citric acid to the total amount of La element in La(NO3)3·6H2O and Ni element in Ni(NO3)2·6H2O was 1.2:1. The mixture was evaporated at 80°C to obtain a wet gel, which was dried at 100°C for 24 h to obtain a dry gel. The mixture was calcined in a muffle furnace, first at a heating rate of 10°C / min to 380°C for 1 h, then at a heating rate of 10°C / min to 850°C for 6 h, and then at a heating rate of 10°C / min to 600°C for reduction for 1 h, with a hydrogen rate of 20 mL / min to obtain Ni / La2O3.

[0094] Comparative Example 3

[0095] This comparative example provides a core-shell structure catalyst and a preparation method thereof, which are as follows:

[0096] 24 mL of ammonia water was added to 50 mL of ethanol and 40 mL of water, the mixture was stirred at 30°C for 10 min, 6 mL of tetraethyl silicate (TEOS) was added, and the mixture was stirred at 30°C for 3 h. The resulting material was centrifuged, washed, and dried in a drying oven at 60°C for 12 h.

[0097] Comparative Example 4

[0098] This comparative example provides a core-shell structure catalyst and a preparation method thereof, which are as follows:

[0099] S1. Dissolve 5 g of Ce(NO3)3·6H2O in 5 mL of water and 5 mL of propionic acid and then add 90 mL of ethylene glycol for the first mixing. The temperature of the first mixing is 30°C and the time of the first mixing is 30 min. Perform a hydrothermal reaction at a temperature of 200°C and a time of 10 h. Wash by centrifugation, dry at 100°C for 24 h, and heat to 700°C at a heating rate of 10°C / min for the first calcination for 5 h.

[0100] S2, 0.02 mol of spherical cerium oxide, 0.02 mol of La(NO3)3·6H2O, 0.02 mol of Ni(NO3)2·6H2O and 50 mL of ethanol were mixed for the second time at a mixing temperature of 30°C and a mixing time of 30 min. Citric acid was then added, and the molar ratio of citric acid to the total amount of La element in La(NO3)3·6H2O and Ni element in Ni(NO3)2·6H2O was 2.2:1. The mixture was evaporated at 90°C to obtain a wet gel, which was dried at 100°C for 12 h to obtain a dry gel. The mixture was calcined for the second time in a muffle furnace, heated to 450°C at a heating rate of 10°C / min and calcined for 1 h, then heated to 900°C at a heating rate of 10°C / min and calcined for 6 h, heated to 600°C at a rate of 10°C / min for reduction for 1 h, and the hydrogen rate was 20 mL / min to obtain a catalyst.

[0101] XPS and BET were used to detect the catalysts prepared in the examples and comparative examples. The specific results are shown in Table 1.

[0102] Table 1

[0103]

[0104]

[0105] Test Case

[0106] The catalysts prepared in the examples and comparative examples were subjected to catalytic tests. The specific catalytic process was as follows: the catalyst was supported by quartz wool and placed in the middle of a quartz tube (600 mm in length and 25 mm in diameter), and the quartz tube was placed in the hydrothermal zone of a vertical hydrothermal furnace. The amount of catalyst used in each experiment was 50 mg. CO2 (7.5 mL / min) and N2 (41.4 mL / min) were introduced. C7H8 was used as a model tar compound and injected into the reaction system at a speed of 5.08 μL / min through an injection pump. Toluene was gasified (1.07 mL / min as a gas component) through a heating belt (180°C) device and then entered the reactor together with a mixture of CO2 and N2. The molar ratio of C7H8 to CO2 was 1:7. The product was determined by online gas chromatography. The product analysis system is an online gas chromatograph (GC, 7890A, Agilent Technologies, USA) equipped with a Carboxen 1000 packed column and a DB-5 capillary column, wherein the injection port temperature of the packed column is maintained at 250°C, the column temperature is maintained at 80°C, and the injection port temperature of the capillary column is maintained at 300°C; small molecule gas products including H2, CO and CO2 are analyzed using a Carboxen 1000 packed column and a TCD detector, while toluene is measured using a DB-5 capillary column and a flame ionization detector (FID).

[0107] The conversion rate of toluene, the conversion rate of carbon dioxide, the selectivity of carbon monoxide, and the selectivity of hydrogen are calculated according to the following formulas:

[0108] The conversion rates of C7H8 and CO2, and the yields of H2 and CO are calculated as follows:

[0109]

[0110] The catalysts prepared in the examples and comparative examples were tested, and Table 2 shows the catalytic effects of the catalysts after 48 hours of use.

[0111] Table 2

[0112]

[0113]

[0114] The catalyst in the present invention can still be used normally after 48 hours without failure, indicating that the catalyst has good stability. From the conversion rate and yield of specific gases, it can be seen that the catalyst prepared by the present invention has better conversion rate and selectivity.

[0115] Carbon deposits

[0116] The carbon deposition conditions of Example 1 and Comparative Examples 1 and 2 were analyzed, and the results are shown in the figure.

[0117] from Figure 7 It can be seen that Ni / La2O3-CeO2-NP in Comparative Example 1 and Ni / La2O3 in Comparative Example 2 have a sharp carbon peak at around 25-26°, which is graphite carbon, not amorphous carbon. Graphite carbon is more likely to cause catalyst deactivation than amorphous carbon because the former is difficult to be consumed by active oxygen species. x -NS does not have this peak, which proves that the catalyst prepared by the present invention is not prone to carbon deposition.

[0118] from Figure 8 It can be seen that the I D / I G The values ​​are 1.13, 0.93 and 0.69 respectively. It can be seen that the carbon deposition on the surface of Ni@CeLaOx-NS has the lowest graphitization degree, which indicates that the growth of carbon deposition on the catalyst is restricted, which also explains the excellent activity and stability of Ni@CeLaOx-NS.

[0119] from Fig. 9It can be seen that the mass losses of Ni@CeLaOx-NS, Ni / La2O3-CeO2-NP and Ni / La2O3 are 5%, 17% and 30%, respectively, which indicates that Ni@CeLaOx-NS can inhibit the nucleation and growth of carbon deposits.

[0120] from Fig.10 It can be seen that previous studies have shown that the weight loss of the catalyst after the reaction due to thermal decomposition below 500°C and above 500°C is amorphous carbon deposition and graphite carbon deposition, respectively. The weight loss of the Ni@CeLaOx-NS catalyst mainly occurs before 500°C, mainly due to the oxidation of amorphous carbon, and the other catalysts all show graphite carbon oxidation peaks. Therefore, the Ni@CeLaOx-NS catalyst has stronger resistance to carbon deposition.

[0121] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A core-shell catalyst, It is characterized in that The core is a spherical cerium oxide with a lattice distortion, and the shell consists of La 2 O 3 and Ni; In the spherical cerium oxide with lattice distortion, Ce 3+ Content is 18-25wt%, Ce 4+ The content is 72-85wt%.

2. The catalyst according to claim 1, It is characterized in that The Ce element and La in the spherical cerium oxide 2 O 3 The molar ratio of La element to Ni element is (0.03-0.08):0.02:0.02, preferably (0.038-0.06):0.02:0.

02.

3. The catalyst according to claim 1 or 2, It is characterized in that The shell layer of the catalyst also includes Co; When Co is contained, the Ce element, La 2 O 3 The molar ratio of La element, Ni element and Co element is (0.03-0.08):(0.01-0.02):(0.01-0.02):(0.005-0.008).

4. The catalyst according to any one of claims 1 to 3, It is characterized in that The specific surface area of ​​the catalyst is 35-45m 2 ·g -1 , pore volume is 0.14-0.25cm 3 ·g -1 , pore size is 20-25nm.

5. A method for preparing a core-shell catalyst, It is characterized in that The preparation method comprises: S1, adding a cerium source to a first solvent, mixing for a first time, performing a hydrothermal reaction, and then performing a first calcination to obtain spherical cerium oxide; S2, mixing the spherical cerium oxide, lanthanum source, nickel source, citric acid and the second solvent for a second time, drying to obtain a gel, calcining for a second time, and reducing to obtain a catalyst with a core-shell structure.

6. The preparation method according to claim 5, It is characterized in that In S1, the cerium source is an inorganic salt containing cerium, preferably Ce(NO 3 ) 3 6H 2 O、Ce(NO 3 ) 3 、CeCl 3 At least one of; and / or, the first solvent comprises water, an organic acid and ethylene glycol; Optionally, the dosage ratio of the cerium source to water is (5-6):(5-7), and the unit is g / mL; Optionally, the volume ratio of water, organic acid and ethylene glycol is 5:(5-7.5):(90-100); Optionally, the organic acid comprises acetic acid and / or propionic acid.

7. The preparation method according to claim 5 or 6, It is characterized in that The temperature of the hydrothermal reaction is 155-165°C and the time is 7.5-8.5h; And / or, the temperature is raised to 550-650° C. at a heating rate of 5-10° C. / min for a first calcination for 5-7 hours.

8. The preparation method according to any one of claims 5 to 7, It is characterized in that In S2, the molar ratio of the Ce element in the spherical cerium oxide, the La element in the lanthanum source, and the Ni element in the nickel source is (0.03-0.08):0.02:0.02, preferably (0.038-0.06):0.02:0.02; Optionally, in S2, when the spherical cerium oxide, lanthanum source, nickel source, cobalt source, citric acid and the second solvent are mixed for the second time, the molar ratio of the Ce element in the spherical cerium oxide, the La element in the lanthanum source, the Ni element in the nickel source and the Co element in the cobalt source is (0.03-0.08):(0.01-0.02):(0.01-0.02):(0.005-0.008); Optionally, the lanthanum source is an inorganic salt containing lanthanum, preferably La(NO 3 ) 3 6H 2 O、La(NO 3 ) 3 、LaCl 3 At least one of; Optionally, the nickel source is an inorganic salt containing nickel, preferably Ni(NO 3 ) 2 6H 2 O.Ni(NO 3 ) 2 、NiCl 2 At least one of; Optionally, the cobalt source is an inorganic salt containing cobalt, preferably Co(NO 3 ) 2 6H 2 O、Co(NO 3 ) 2 、CoCl 2 At least one of; Optionally, the molar ratio of the citric acid to the sum of the La element in the lanthanum source and the Ni element in the nickel source is 1-2:1, preferably 1.2-1.5:

1.

9. The preparation method according to any one of claims 5 to 8, It is characterized in that Raise the temperature to 350-400°C at a heating rate of 5-10°C / min and calcine for 1-1.5h, then raise the temperature to 800-870°C at a heating rate of 5-10°C / min and calcine for 5-7h; And / or, the reduction conditions include: heating to 600-700°C at a rate of 5-15°C / min for reduction, for 1-2.5h, and a hydrogen rate of 15-25mL / min.

10. The catalyst according to any one of claims 1 to 4 or the catalyst prepared by the preparation method according to any one of claims 5 to 9 in tar and CO 2 Application in reorganization.